Smart Grids and Distributed Generation - Dorin BICĂ; Lucian Ioan DULĂU (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2018)
This paper describes the main characteristics of Smart Grids and distributed generation. Smart Grids can be defined as a modernization of the power system so it monitors, protects and automatically optimizes the operation of its interconnected elements (power plants, transmission and distribution system, industrial and residential loads). Distributed generation (DG) refers to the production of electricity near the consumption place using renewable energy sources. A load flow analysis is performed for the IEEE14 system in which a DG source (a 5MW wind turbine) is added that is on-grid or off-grid. The power losses are determined for these two cases.